Women's bodies, women's wisdom : creating physical and emotional health and healing - Northrup, Christiane (Bantam Books, 2020)
"Emphasizing the body's innate wisdom and ability to heal, Women's Bodies, Women's Wisdom covers the entire range of women's health--from the first menstrual period through menopause. It includes updated information on pregnancy, labor, and birth, sexuality, nutrition, hormone replacement therapy, treating fibroids, avoiding hysterectomy, and maintaining breast and menstrual health. Fully revised and updated to include the very latest treatment innovations and research data, and reflecting today's woman's proactive involvement in her own health care, this important new edition will help women everywhere enjoy vibrant health with far fewer medical interventions."--Page 4 of cover.